Development of Electrolytes for Single Crystal NMC532/Artificial Graphite Cells with Long Lifetime. Issue 3 (1st January 2018) - Li, Jing; Li, Hongyang; Stone, Will; Glazier, Stephen; Dahn, J. R.
Abstract : NMC532/artificial graphite cells using single crystal NMC532 active material can have excellent long term lifetime at 4.4 V and elevated temperature if appropriate electrolytes are used. However, electrolytes developed earlier for these cells and reported in the literature cannot support even C/2 rates during charging without unwanted lithium plating at room temperature. This work is thus focused on the development of new electrolytes for single crystal NMC532/artificial graphite cells that can yield long lifetime and support higher charging rates. Ex-situ and in-situ gas measurements, ultra-high precision coulometry, isothermal microcalorimetry, lithium plating tests and long term cycling tests were used for the screening of electrolytes. Electrolytes with 2% vinylene carbonate (VC) + 1% ethylene sulfate (DTD) additives or 2% fluoroethylene carbonate (FEC) + 1% DTD additives yield single-crystal NMC532/graphite cells with long lifetime that can support C-rate charging at 20°C.